2022
DOI: 10.1021/jacs.2c05447
|View full text |Cite
|
Sign up to set email alerts
|

Heteroanionic Control of Exemplary Second-Harmonic Generation and Phase Matchability in 1D LiAsS2–xSex

Abstract: The isostructural heteroanionic compounds β-LiAsS2–x Se x (x = 0, 0.25, 1, 1.75, 2) show a positive correlation between selenium content and second-harmonic response and greatly outperform the industry standard AgGaSe2. These materials crystallize in the noncentrosymmetric space group Cc as one-dimensional 1/∞ [AsQ2]− (Q = S, Se, S/Se) chains consisting of corner-sharing AsQ3 trigonal pyramids with charge-balancing Li+ atoms interspersed between the chains. LiAsS2–x Se x melts congruently for 0 ≤ x ≤ 1.75, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Nonlinear optical (NLO) crystals enable the production of coherent lasers owing to their frequency conversion ability, serving as the core component of solidstate lasers in modern optical science and technology. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] To date, notable infrared (IR) NLO crystalline materials include commercially available AgGaQ 2 (Q = S, Se), and ZnGeP 2 because of their large polarizability microstructures that can lead to remarkable second-harmonic generation (SHG) responses and superior optical transparency window in the IR range. [19][20][21] However, they suffer from inherent deficiencies, such as the relatively low laser-induced damage thresholds (LIDTs) of AgGaQ 2 or the unexpected multi-phonon absorption of ZnGeP 2 , hindering their wide application in high-power laser field.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear optical (NLO) crystals enable the production of coherent lasers owing to their frequency conversion ability, serving as the core component of solidstate lasers in modern optical science and technology. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] To date, notable infrared (IR) NLO crystalline materials include commercially available AgGaQ 2 (Q = S, Se), and ZnGeP 2 because of their large polarizability microstructures that can lead to remarkable second-harmonic generation (SHG) responses and superior optical transparency window in the IR range. [19][20][21] However, they suffer from inherent deficiencies, such as the relatively low laser-induced damage thresholds (LIDTs) of AgGaQ 2 or the unexpected multi-phonon absorption of ZnGeP 2 , hindering their wide application in high-power laser field.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has extensively studied noncentrosymmetric low-dimensional materials to gain insights into the underlying structure–property relationships behind NLO properties such as SHG and THG. Here, we define dimensionality as the number of crystallographic axes in which there is long-range covalent bonding. In particular, we found that the one-dimensional (1-D) family AAsQ 2 (A = Li, Na, K; and Q = S, Se) has some of the highest SHG outputs in the IR to date (648 pm/V for γ-NaAs 0.95 Sb 0.05 Se 2 ) and that the two-dimensional (2-D) family AGaM′Q 4 (A = K, Rb, Cs, Tl; M′ = Ge, Sn; and Q = S, Se) outperforms the THG of industry-standard material AgGaS 2 by up to four times . Theoretical studies on the chalcoarsenates show that the reduced dimensionality leads to a high degree of separation between adjacent chain orbitals, flattening the electronic bands and increasing the overall nonlinear response .…”
Section: Introductionmentioning
confidence: 96%
“…For M/F-IR NLO materials, chalcogenides and pnictides have been demonstrated as the alternated systems, and AgGaQ 2 (Q = S, Se) , and ZnGeP 2 (ZGP) with large NLO responses and wide optical transmission ranges have been commercially applied. However, the intrinsic defects (especially for the small band gaps) in these materials, e.g., low laser-induced damage threshold (LIDT) in AgGaS 2 (AGS) and AgGaSe 2 (AGSe) and strong two-photon absorption at ∼1 μm in ZGP have seriously limited their applications in modern laser technologies . Hence, it is urgently needed to develop new IR NLO materials with a balanced large SHG response and a broad band gap …”
Section: Introductionmentioning
confidence: 99%